Peningkatan Kemampuan Kognitif melalui Bermain Playdough - Susilowati, Endang (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2017)
This study aims to determine the effectiveness of playdough media to improve childrens cognitive abilities. The design of this study used classroom action research. The results show that for the